Stem cells for enhancing recovery after stroke: a review - England, Timothy J.; Martin, Paul; Bath, Philip M.W. (2009)
The potential application for stem cell therapy is vast, and development for use in ischaemic stroke is still in its infancy. Access to stem cells for research is contentious; however, stem cells are obtainable from both animal and human. Despite a limited understanding of their mechanisms of action, clinical trials assessing stem cells in human stroke have been performed. Trials are also underway evaluating haematopoietic precursors mobilised with granulocyte-colony stimulating factor, an approach offering an autologous means of administrating stem cells for therapeutic purposes. This review summarises current knowledge in regard to stem cells and their potential for helping improve recovery after stroke.